Is adaptive treatment planning in multi-catheter interstitial breast brachytherapy necessary?. (December 2019) - Kallis, Karoline; Ziegler, Marc; Lotter, Michael; Kreppner, Stephan; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph
Highlights: Comparison of planning CT and follow-up CT resulted in a mean ΔCI of 3.10 ± 3.17%. 4% of considered patients classified as critical cases. Loss of CI in 36% of evaluated patients connected to ΔDP >2.5 mm. No correlation of deviations to breast volume, patients' age, PTV or catheter length. Challenging to define precise thresholds and indicate explicit parameters to trigger re-planning. Abstract: Purpose: For 55 patients treated with interstitial multi-catheter breast brachytherapy the need for adaptive treatment planning was assessed. Methods and materials: For all patients a treatment planning computed tomography (CT) and a follow-up CT were acquired and used for the retrospective evaluation. Keeping dwell time and dwell positions constant, the treatment plan assessed directly after catheter implantation was compared to the situation 48 h after implantation. Both manual catheter reconstructions, based on the planning and follow-up CT, were rigid registered to each other and the resulting deviations analyzed, like the difference between corresponding dwell positions (ΔDP) or the discrete Fréchet distance. Further, the dosimetric changes, e.g., coverage index (ΔCI), conformal index (ΔCOIN) and dose non-uniformity ratio (ΔDNR) were considered for a deformed planning target volume (PTV) and the rigid warped PTV structure. The PTV was deformed according to the vector field estimated between the two acquired CTs. Results: Over all patients with rigid aligned CTs a mean ΔDP, ΔCI, ΔCOIN and ΔDNR were determined to 2.41 ± 1.73 mm, 3.10 ± 3.17%, 0.009 ± 0.007 and 0.036 ± 0.040, respectively. Considering the deformed PTV ΔCI was estimated to 5.05 ± 4.14 %. Conclusion: In conclusion, in 4% of the cases re-planning would have been beneficial to ensure the planned dose delivery. Large PTV changes or large DP deviations were found to be the main reasons for dosimetric variations.